The Role of Opportunity Recognition and Personality in Entrepreneurial Intention in Mediation by Risk Aversion - Septihani Wijaya; Hetty Tunjungsari (CV ODIS, 2023)
Entrepreneurship is a global practice and phenomenon because it contributes to economic growth, maintenance of social stability, and reduction of unemployment rates country. Given the significant role of entrepreneurial intent, which has been widely studied, it leads to the understanding that the intention to launch a business stems from environment-oriented and people-oriented characteristics. This study focuses on people-oriented features and answers how and why this personality influences entrepreneurial intentions. This study aimed to determine the effect of opportunity recognition and personality on entrepreneurial intention by risk aversion as the mediates factor. The sampling technique used is non-probability sampling, and the sample selection technique used is purposive sampling. Data collection used an online google form questionnaire with a total sample of 200 respondents. The data analysis technique used is Structural Equation Modeling (SEM). Data processing is done using SmartPLS. The model in this study was university students in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, dan Bekasi). The results of this study show that opportunity recognition and personality positively affect entrepreneurial intention by risk aversion as the mediates factor.